MacroH2A1.2 inhibits prostate cancer-induced osteoclastogenesis through cooperation with HP1α and H1.2. Issue 43 (25th October 2018) - Kim, Jin-Man; Shin, Yonghwan; Lee, Sunyoung; Kim, Mi; Punj, Vasu; Shin, Hong-In; Kim, Kyunghwan; Koh, Jung-Min; Jeong, Daewon; An, Woojin
Abstract Osteoclasts are multinuclear bone-resorbing cells that differentiate from hematopoietic precursor cells. Prostate cancer cells frequently spread to bone and secrete soluble signaling factors to accelerate osteoclast differentiation and bone resorption. However, processes and mechanisms that govern the expression of osteoclastogenic soluble factors secreted by prostate cancer cells are largely unknown. MacroH2A (mH2A) is a histone variant that replaces canonical H2A at designated genomic loci and establishes functionally distinct chromatin regions. Here, we report that mH2A1.2, one of the mH2A isoforms, attenuates prostate cancer-induced osteoclastogenesis by maintaining the inactive state of genes encoding soluble factors in prostate cancer cells. Our functional analyses of soluble factors identify lymphotoxin beta (LTβ) as a major stimulator of osteoclastogenesis and an essential mH2A1.2 target for its anti-osteoclastogenic activity. Mechanistically, mH2A1.2 directly interacts with HP1α and H1.2 and requires them to inactivate LTβ gene in prostate cancer cells. Consistently, HP1α and H1.2 have an intrinsic ability to inhibit osteoclast differentiation in a mH2A1.2-dependent manner. Together, our data uncover a new and specific role for mH2A1.2 in modulating osteoclastogenic potential of prostate cancer cells and demonstrate how this signaling pathway can be exploited to treat osteolytic bone metastases at the molecular level.